The Influence of Hybrid Fibers and Nanomaterials (Nano Glass with Nano Slag) on the Behavior of Reactive Powder Concrete - Thanon Dawood, Eethar; Abdullah, Mafaz Hani; Plank, Johann (International Journal of Sustainable Construction Engineering and Technology, 2022)
The new production for reactive powder concrete (RPC) has become an interesting topic due to the dramatic properties that such materials can give. Thus, this study has been prepared to observe the properties of RPC mixes reinforced with micro steel fibers (MSF) by the order of 2% volumetric fractions (vol.). As well, hybrid fibers from MSF, sisal fiber (SIF), and also human hair fibers (HHF) have been included in the RPC mix in the order of 1.5% MSF plus 0.5% SIF, 1.5% MSF plus 0.5% HHF, and 1.5% MSF plus 0.25% SIF plus 0.25% HHF, respectively. Besides, the inclusion of two different nanomaterials combination by 2.5% from Nano glass powder (NG) and 2.5% Nano Iron slag powder(NS) was performed into that reinforced RPC. The preparation of these different RPC mixes was followed by testing them to investigate the performance of such RPC based on the properties of flowability, compressive strength, tensile strength, flexural strength, flexural toughness, and static modulus of elasticity. The results showed that the incorporation of 2%MSF increases the compressive strength, tensile strength, and flexural strength by 6.76%, 12.45%, and 14.34%, respectively, at 90 days. Whereas, the reinforcing of RPC by 1.5% micro steel fibers(MSF) with 0.25% sisal fibers (SIF) and 0.25% human hair fibers(HHF) rises the values of compressive strength, tensile strength, and flexural strength by 5.38%, 11.59%, and 14.05%, respectively, at age of 90 days. Moreover, the uses of nanoparticles as 2.5%NG with 2.5%NS in addition to 2%MSF increase the compressive strength, tensile strength, and flexural strength by 33.09%, 36.05%, and 43.68% at age of 90 days, respectively. The use of 1.5% MSF plus 0.25% SIF plus 0.25% HHF with the mentioned nanoparticles(2.5%NG and 2.5% NS) boosts the best performance by converting such concrete from brittle material to ductile material.